2011
DOI: 10.1093/nar/gkq1333
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic basis for recognition and repair of 8-oxoguanine in DNA by human 8-oxoguanine-DNA glycosylase

Abstract: We have used a stepwise increase in ligand complexity approach to estimate the relative contributions of the nucleotide units of DNA containing 7,8-dihydro-8-oxoguanine (oxoG) to its total affinity for human 8-oxoguanine DNA glycosylase (OGG1) and construct thermodynamic models of the enzyme interaction with cognate and non-cognate DNA. Non-specific OGG1 interactions with 10–13 nt pairs within its DNA-binding cleft provides approximately 5 orders of magnitude of its affinity for DNA (ΔG° approximately −6.7 kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(69 citation statements)
references
References 51 publications
1
68
0
Order By: Relevance
“…Earlier studies indicated that the binding affinity of OGG1 for a lesion containing substrate was decreased when a T:G mismatched base pair was positioned both 5Ј or 3Ј of 8-oxoG (56). In the current study, a 5Ј-flanking T:G mismatched base pair significantly decreased the 8-oxoG base removal of OGG1 in single turnover and pre-steady-state assays (Figs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Earlier studies indicated that the binding affinity of OGG1 for a lesion containing substrate was decreased when a T:G mismatched base pair was positioned both 5Ј or 3Ј of 8-oxoG (56). In the current study, a 5Ј-flanking T:G mismatched base pair significantly decreased the 8-oxoG base removal of OGG1 in single turnover and pre-steady-state assays (Figs.…”
Section: Discussionsupporting
confidence: 63%
“…This is in contrast to E. coli MutM, which is strongly affected by the local sequence context (40). Interestingly, an earlier study suggested that OGG1 interacts with the 8-oxoG-modified substrates more avidly than MutM and was not significantly affected by DNA sequence context (56). Thus, a rapid excision of 8-oxoG by OGG1, regardless of the local DNA sequence, may be due to its high specificity for the cognate substrate.…”
Section: Discussionmentioning
confidence: 82%
“…Various kinds of DNA damage in proximity to 8-oxoG (a mismatch, an abasic site or a single-strand break) also strongly inhibit the excision by OGG1 (42,44), which is regarded as the mechanism for prevention of cytotoxic secondary damage that may arise from attempted repair of such complex lesions. The same could be the reason for the inefficient excision of 8-oxoG situated close to the ends of linear DNA (45,46) or in DNA sequences forming partly single-stranded structures such as hairpins, D-loops or bulges (41,47,48). It has not been clear until now whether, besides the mentioned particular DNA structures, any DNA sequence determinants exist that can influence the catalytic activity of OGG1.…”
Section: Discussionmentioning
confidence: 99%
“…It has not been clear until now whether, besides the mentioned particular DNA structures, any DNA sequence determinants exist that can influence the catalytic activity of OGG1. Measurements of the kinetic parameters in the oligonucleotide substrates have predicted that sequence of 10–13 nt around 8-oxoG has influence on the OGG1 binding and catalytic rates (48). However, because of the major influence of DNA duplex stability on the excision parameters in this system, the significance of these data is difficult to extrapolate to long DNA of highly stable helical structure, as it is found in the genome.…”
Section: Discussionmentioning
confidence: 99%
“… To evaluate the relative contributions of individual DNA elements to the enzyme affinity for long polymeric and oligomeric ligands, a new approach, stepwise increase in ligand complexity (SILC), was developed . Using the SILC, we have analyzed the mechanisms of recognition of DNA by number of DNA‐dependent enzymes: not specific for DNA sequence and structure such as Escherichia coli RecA, specific for DNA structure but not sequence‐dependent such as DNA polymerases of eukaryotes, prokaryotes, viruses, and archaea and human DNA ligase I; specific for DNA containing damages such as human uracil DNA glycosylase, E. coli Fpg and human 8‐oxoguanine DNA glycosylases (OGG1), human apurinic/apyrimidinic endonuclease (AP endonuclease), as well as specific for DNA sequence such as human HIV integrase, topoisomerase I (Topo I), Eco RI restriction endonuclease, and human lactoferrin (LF) . It was shown that complex formation including formation of contacts between specific sequences in all these enzymes cannot provide for either substrate specificity or high enzyme affinity for DNA.…”
Section: Introductionmentioning
confidence: 99%